Relevant aspects of financial control and audit of the budgetary sphere of activity of bodies of internal Affairs of Russia - A. F. Dyatlova; A. A. Popova (Путеводитель предпринимателя, 2020)
In the article various approaches to definition of financial control, which recently plays a significant role in ensuring the efficient activity of bodies of internal Affairs of Russia. The article considers the system of financial control, proposed their own point of view on the content of financial control, as well the place of the departmental financial control and its relationship with the internal financial audit.